Is Islam Compatible with Modernity? An Analysis of Modernity as Modern Civilization - Sukron Kamil (Universitas Islam Negeri Sunan Kalijaga, 2020)
The relation between Islam and modernity as modern civilization is frequently faced contradiction. The disclaimer of a secular state for instance, leads to the debate by which the articulation of some Muslims who reject it is much more than those who accept it. Another example is humanism such as religious freedom and capitalism, although the disclaimers of these two issues are softer than those who denied the nation-state. However, the conceptual analysis points out that Islam is compatible with modernity as modern civilization. The main reason is that Islam was first emerged as a critic against the previous religion that was not engage the social transformation for the Arab society before Islam. Islam is also encouraged contemporary thought and social reform with the concept of ishlah (reform) and tajdid (renewal). If this case is measured based on the dimension of modernity, it obvious that Islam Islam as a teaching/conceptual frame/mindset in this article does not have conflict with it. Islam is in line with the nation state, secular country or secularism itself, democracy as political system, rationalism and empirical science, and capitalism. This paper is expected to strengthen the Integration of Islam as society with the modernity as modern civilization in the East and West countries.